Application of chromosome microarray analysis and karyotyping in diagnostic assessment of abnormal Down syndrome screening results - Han Kang; Lingxi Wang; Xingyu Li; Chonglan Gao; Yamei Xie; Yu Hu (BMC, 2022)
Abstract Background Down syndrome (DS) is the most common congenital cause of intellectual disability and also leads to numerous metabolic and structural problems. This study aims to explore the application value of chromosomal microarray analysis (CMA) and karyotyping in prenatal diagnosis for pregnant women with abnormal DS screening results. Methods The study recruited 1452 pregnant women with abnormal DS screening results including 493 with an enlarged nuchal translucency thickness (NT ≥ 2.5 mm) and 959 with an abnormal second-trimester maternal serum biomarker screening results. They underwent amniocentesis to obtain amniotic fluid for CMA and karyotyping. Results CMA identified 74/1452 abnormal results, which was more efficient than karyotyping (51/1452, P < 0.05.) CMA is equivalent to traditional karyotyping for identifying aneuploidies. Compared to karyotyping CMA identified 1.90% more copy number variants (CNVs) ranging from 159Kb to 6496Kb. However, 34.4% of them were recurrent pathogenic CNVs associated with risk of neurodevelopmental disorders. CMA identified 13 variants of uncertain significance (VUS) results and 1 maternal uniparental disomy (UPD) of chromosome 7. Karyotyping identified 3 mosaic sex chromosome aneuploidy and 4 balanced translocation which could not be identified by CMA. In enlarged NT group, karyotyping identified 80.9% abnormal results while in serum screening group karyotyping identified 35.7%. However, the incidence of pathogenic/likely pathogenic (P/LP) CNVs was nearly the same in both groups. That was because aneuploidies and gross duplication/deletion were previously screened out by NT scan. Conclusions CMA and karyotyping have both advantages and disadvantages in prenatal diagnosis of pregnant women with abnormal DS screening results. However, there was not enough evidence to support routine CMA in pregnant women with abnormal DS screening results.